An Electronic Traceability System for an Indonesian Fresh Fruit Supply Chain - Vanany, Iwan; Andri, Kuntoro Boga; Mardiyanto, Ronny; Puspita, Niniek Fajar; Winarsih, Wiwik Heny (IPTEK Journal of Proceedings Series, 2014)
Nowdays, traceability system for agriculture comodity is mandatory requirements in some countries such as Japan, United States, and all European countries. All export agricultural companies must applied traceability system to fulfill the mandates of goverments market requirements. Traceability system also has beneficials to reduce products return and improve efficiencies and effectiveness their inventory. Electronic traceability system is relatively new and is believed by many experts to have the advantages than paper-based traceability system such as: integration of data to multiple users, the accuracy of data input and control and monitoring easier and faster. Although the recent problems of traceability becomes the important issues in food and agriculture supply chain, but a few researchers to design and implement electronic traceability system especially to integrate multi-user and in supply chain contex. This paper develop the electronic traceability system products including software for electronic traceability system and barcode technology. Unified Modelling Language (UML) is used to design traceabilty system model that was described a usecase, state and sequence diagram. Based on these models, electronic traceability system was developed by adopting XAMPP control panel. Indonesian mangosteen and manggo fruits were chosen as a case study in order to validate electronic traceability system. The results showed that the electronic traceability system product is relatif support to helps members of supply chain to complete their traceability system capabilities for the benefit of mangosteen and mango exports